Investigation of pharmaceutical compounds (Metronidazole, Rosuvastatin and Codeine phosphate) removal by Synechocystis sp. PCC6803 microalga. (June 2022) - Bahman, Mahsa; Jalili, Hasan; Etesam, Masoudeh; Amrane, Abdeltif
Abstract: The uncontrolled entry of pharmaceutical compounds (PCs) into water sources causes irreversible damages to microorganisms. This study aimed to evaluate the capability of Synechocystis sp. PCC6803 microalga to remove three PCs, namely Metronidazole in 1, 3, and 5 mg/L, Rosuvastatin in 200, 400, and 600 mg/L, and Codeine phosphate in 50, 150, and 250 mg/L. These PCs have not been effectively removed by chemical and physical wastewater treatment methods. Adding Metronidazole to the culture medium resulted in a 70% reduction in biomass production; while the amount of protein produced at the concentration of 5 mg/L increased about 3 times compared to the control culture. The culture medium containing 600 mg/L Rosuvastatin increased the total lipid production by more than 50%. The biomass and protein produced in culture medium containing Codeine phosphate were not significantly different compared with the control. Moreover, the drugs removal efficiency of Synechocystis was 80% for Metronidazole and almost 100% for Rosuvastatin and Codeine Phosphate. Metronidazole, which is a lipophilic drug, bonds to the cell surface of microalgae through the formation of chemical bonds between its aromatic rings and functional groups on the surface of extracellular substrates. However, Rosuvastatin and Codeine phosphate which are hydrophilic drugs can enter the cells, where they are degraded by intra-cellular enzymatic mechanism; thus, they were removed by cell biodegradation mechanism in cells. The findings of this study can be potentially used in e.g., hospital wastewater treatment sustainably and economically using microalgae in the future. Highlights: Synechocystis effectively removed Metronidazole, Rosuvastatin and Codeine phosphate. 80% of Metronidazole was removed by adsorption on the microalga cells surface. Rosuvastatin and Codeine phosphate were 100% degraded in the microalga cells. Metronidazole increased protein by 50% and Rosuvastatin increased lipid by 50%.